Kreativitas Guru IPA Kelas VII Dan VIII Dalam Penyusunan Penilaian Autentik Di SMP Negeri 1 Pecangaan Jepara Semester Gasal Tahun Ajaran 2014/2015 - Setyanto, Ade Fiqri; , Dra. Hariyatmi, M.Si (2015)
Authentic assessment is an assessment process from beginning to the end in the learning process with a series of several specific assessment. On arranging authentic assessment is required creativity to process rubric which is available into a real assessment. This research is aim to determine the creativity science teachers VII and VIII class in arranging of authentic assessment at state junior high school of Pecangaan 1 Jepara odd semester of academic year 2014/2015. This research is a qualitative descriptive study using a case study approach, data collection techniques with the study of documentation, interviews and observation. Data obtained from arranging of assessment instruments in the RPP which has been prepared by science teachers at state junior high school of Pecangaan 1 Jepara odd semester academic year 2014/2015. The data has been analyzed using descriptive statistics. Based on the results of the research shown that creativity in arranging authentic assessment was ungood (49.33%). This is can be looked from the arranging of assessment observations (76.53%), self-assessment (68.99%), multiple choice assessment (49.66%), description of assessment (64.1%), assessment assignment (13.34%) , performance assessment (76.37%), project assessment (30%) and assessment of the portfolio (15.71%). An appropriatability of arranging authentic assessment with the criteria that have been standardized are unfavourable (49.24). It can be concluded that creativity and appropriatability grade of science teachers VII and VIII class in arranging authentic assessment in state junior high school of Pecangaan 1 Jepara odd semester academic year 2014/2015 are unfavorable.